Scenarios for the agricultural sector in South and East Mediterranean countries by 2030 - Saad Belghazi (Center for Social and Economic Research (CASE), 2012)
The paper builds predictive scenarios for the agricultural sector of eleven Mediterranean countries (Med 11), namely Algeria, Egypt, Israel, Jordan, Lebanon, Libya, Morocco, Palestine, Syria, Tunisia and Turkey. First, it assesses the performance trends of the Med 11 agricultural sector with a focus on production, consumption and trade patterns, incentives, trade protection policies and trade relations with the EU and productivity dynamics and their determinants. Secondly, it presents four scenarios based on the main value chains of the agriculture sector of Med 11: animal products, fruits and vegetables, sugar and edible oil, cereals and fish and other sea products. The four scenarios are: business as usual, Mediterranean One global Player, the Euro Mediterranean Area under threat and the EU and Med 11 as Regional Player.
Keywords: Q11; Q17; Q18; C53; 330; Agriculture; Prospective; East and South Mediterranean; Agricultural Trade and Incentives Policy; Growth; Productivity; Structural change; Landwirtschaft; Agrarproduktion; Agrarpolitik; Agraraußenhandel; Internationale Wirtschaftsbeziehungen; Szenariotechnik; Mittelmeerraum; Mittlerer Osten; Nordafrika